Revealing Operando Transformation Dynamics in Individual Li-ion Electrode Crystallites Using X-Ray Microbeam Diffraction - van Hulzen, Martijn; Ooms, Frans G. B.; Wright, Jonathan P.; Wagemaker, Marnix (Frontiers in Energy Research, 2018)
For the development of next generation batteries it is important to understand the structural changes in electrodes under realistic non-equilibrium conditions. With microbeam X-ray diffraction it is possible to probe many individual electrode grains concurrently under non-equilibrium conditions in realistic battery systems. This makes it possible to capture phase transformation behaviour that is difficult or even impossible with powder diffraction. By decreasing the X-ray beam size, the diffraction powder rings fall apart in the (hkl) reflections belonging to individual electrode crystallites. Monitoring these reflections during (dis)charging provides direct insight in the transformation mechanism and kinetics of individual crystallite grains. Here the operando microbeam diffraction is applied for two different cathode materials, LiFePO_4 (LFP) displaying a first order phase transformation and LiNi_1/3Co_1/3Mn_1/3O_2 (NCM) displaying a solid solution transformation. For LFP four different phase transformation mechanisms are distinguished within a single crystallite: (1) A first order phase transformation without phase coexistence, (2) with phase coexistence, (3) a homogeneous solid solution phase transformation and (4) an inhomogeneous solid solution crystal transformation, whereas for NCM only type (3) is observed. From the phase transformation times of individual crystallites, the local current density is determined as well as the active particle fractions during (dis)charge. For LFP the active particle fraction increases with higher cycling rates. At low cycling rates the active particle fraction in NCM is much larger compared to LiFePO_4 which appears to be related to the nature of the phase transition. In particular for LFP the grains are observed to rotate during (dis)charging, which can be quantified by microbeam diffraction. It brings forward the mechanical working of the electrodes due to the volumetric changes of the electrode material possibly affecting electronic contacts to the carbon black conducting matrix. These results demonstrate the structural information that can be obtained under realistic non-equilibrium conditions, combining local information on single electrode crystallites, as well as global information through the observation in many crystallites concurrently. This provides new and complementary possibilities in operando battery research, which can contribute to fundamental understanding as well as the development of electrodes and electrode materials.